Excavating the land of Jesus : how archaeologists study the people of the gospels - Strange, James Riley (Grand Rapids William B. Eerdmans Publishing Company, 2023)
"A textbook about the archaeology of first-century Roman Galilee and how it relates to the gospels"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Antiquities; Archaeology; Galilee (Israel) -- Antiquities